2020
DOI: 10.1155/2020/1719564
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation and Adolescent Altruistic Behaviors in Social Networks

Abstract: Social networks provide a convenient place for people to interact; members in social networks may create new connections or break existing connections, driving the evolution of complex network structure. Dynamics in social networks, such as opinion formation and spreading dynamics, may result in complex collective phenomena. This paper conducts a survey on 495 students from six schools in Shaanxi, Henan, and Zhejiang provinces and discusses the impact of self-presentation on adolescent network altruistic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The study in question did report a relevant measure of SoMe use, focused on “altruistic behaviors in social networks,” and reported a non-significant association between these factors (Zhu et al, 2020 ). However, the description of these behaviors seemed to be outside our definition of OPBs, covering dimensions related to “sharing with others the experiences and perceptions of their lives in social networks,” “creating a platform for a person to communicate, “sharing your successful learning experience with others in social networks,” and “network warning” (Zhu et al, 2020 , p. 4). Although these dimensions may indirectly be conduit for OPB, they are not prosocial behaviors per se .…”
Section: Resultsmentioning
confidence: 99%
“…The study in question did report a relevant measure of SoMe use, focused on “altruistic behaviors in social networks,” and reported a non-significant association between these factors (Zhu et al, 2020 ). However, the description of these behaviors seemed to be outside our definition of OPBs, covering dimensions related to “sharing with others the experiences and perceptions of their lives in social networks,” “creating a platform for a person to communicate, “sharing your successful learning experience with others in social networks,” and “network warning” (Zhu et al, 2020 , p. 4). Although these dimensions may indirectly be conduit for OPB, they are not prosocial behaviors per se .…”
Section: Resultsmentioning
confidence: 99%
“…The results of their study indicated that ingratiation had a significant positive effect on counterproductive work behaviour in manufacturing companies in China. Zhu et al [70] examined the relationship between self-presentation and adolescent altruistic behaviour. Their result revealed that self-presentation predicted altruistic behaviour of adolescents in China.…”
Section: -3-impression Management and Employee Contextual Performancementioning
confidence: 99%